Evaluation of Accreditation-Based School Management in Improving Quality of Educationat SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District - Warni Tune Sumar; Intan Abdul Razak; Nina Lamatenggo (Universitas Negeri Padang, 2020)
Objective of this study was to find out an obvious description for the evaluation of accreditation-based school management in improving the quality ofeducation at SMP (Junior High School) Widyakrama in Telaga Biru Sub-district, Gorontalo District by studying four indicators which were: (1) curriculum management at SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District, (2) human resource management at SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District, (3) facility and infrastructure management at SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District, and (4) education financing management at SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District. This research applied an evaluation done quantitatively, qualitatively, and descriptively in a percentage. Research samples were school principal, teachers, employees, parents, committee, and students that were 28 in total. Techniques of data collection used questionnaire, observation, interview, and documentation. Research findings were as followed: (1) the curriculum management at SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District achieved average score of 97.7 or 66.31 in effective category, (2) the human resource management at SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District achieved average score of 98,14 or 83.5 in effective category , (3) the facility and infrastructure management at SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District achieved average score of 97.14 or 82.3 in effective category, and (4) the education financing management at SMP Widyakrama in Telaga Biru Sub-district, Gorontalo District achieved average score of 98 or 83,33 in effective category